Sinus tarsi incision open method versus minimally invasive locking calcaneal nail for operative management of displaced intra-articular calcaneal fractures: A retrospective, matched pairs, single center, comparative analysis - Jennifer M. So, DPM; Thomas S. Roukis, DPM, PhD, FACFAS; Jason A. Piraino, DPM, MS, FACFAS (Foot & Ankle Surgery: Techniques, Reports & Cases, 2024)
Background: The sinus tarsi incision open approach for plate and/or screw fixation of displaced intra-articular calcaneal fractures is a well-accepted method. A more recently introduced method employing a minimal incision approach and a locking intra-medullary nail construct exists. This matched pairs analysis compares the fracture reduction capacity of the minimally-invasively placed calcaneal locking nail with the sinus tarsi incision open method. Methods: Twenty-two displaced intra-articular calcaneal fractures were matched for age, gender, laterality, Essex-Lopresti classification, and soft-tissue injury and managed with either sinus tarsi incision open method (group 1, N=11) or minimally-invasively placed calcaneal locking nail (group 2, N=11). Intra-operative tourniquet time and total operative duration were collected. Follow-up included Gissane and Böhler radiological assessments. Results: Significant differences between groups were identified for tourniquet time (p=0.000002) where group 1 had greater use of and duration of tourniquet control, lower pre-operative Böhler angle (p=0.02973), lower post-operative final follow-up Böhler angle (p=0.000992), lower change between pre- and post-operative final follow-up Böhler angle (p=0.02823), and lower change between pre- and post-operative final follow-up Gissane angle (p=0.01432) than group 2. Conclusion: We identified superior Gissane and Böhler angle restoration with the use of the minimally-invasively placed calcaneal locking nail compared to the sinus tarsi incision open method. Ultimately, a larger patient population is necessary to determine whether the minimally-invasively placed calcaneal locking nail warrants replacing the sinus tarsi incision open approach for operative management of displaced intra-articular calcaneal fractures. Level of evidence: III-Therapeutic study: Retrospective comparative analysis at a single institution Category: Trauma, Surgical Management